Adapting Rational Unified Process (RUP) approach in designing a secure e-Tendering model - Mohd, Haslina; Robie, Muhammad Afdhal Muhammad; Baharom, Fauziah; Muhd Darus, Norida; Saip, Mohamed Ali; Yasin, Azman (2016)
e-Tendering is an electronic processing of the tender document via internet and allow tenderer to publish, communicate, access, receive and submit all tender related information and documentation via internet.This study aims to design the e-Tendering system using Rational Unified Process approach.RUP provides a disciplined approach on how to assign tasks and responsibilities within the software development process. RUP has four phases that can assist researchers to adjust the requirements of various projects with different scope, problem and the size of projects. RUP is characterized as a use case driven, architecture centered, iterative and incremental process model. However the scope of this study only focusing on Inception and Elaboration phases as step to develop the model and perform only three of nine workflows (business modeling, requirements, analysis and design). RUP has a strong focus on documents and the activities in the inception and elaboration phases mainly concern the creation of diagrams and writing of textual descriptions. The UML notation and the software program, Star UML are used to support the design of e-Tendering. The e-Tendering design based on the RUP approach can contribute to e-Tendering developers and researchers in e-Tendering domain.In addition, this study also shows that the RUP is one of the best system development methodology that can be used as one of the research methodology in Software Engineering domain related to secured design of any observed application.This methodology has been tested in various studies in certain domains, such as in Simulation-based Decision Support, Security Requirement Engineering, Business Modeling and Secure System Requirement, and so forth.As a conclusion, these studies showed that the RUP one of a good research methodology that can be adapted in any Software Engineering (SE) research domain that required a few artifacts to be generated such as use case modeling, misuse case modeling, activity diagram, and initial class diagram from a list of requirements as identified earlier by the SE researchers